REFORMULASI PENGANGKATAN TENAGA HONORER KATEGORI 1 (K1) dAN KATEGORI 2 (K2) PROVINSI JAWA TENGAH - .Hartiwiningsih, Hartiwiningsih (Faculty of Law, Universitas Sebelas Maret, 2014)
This study on the implementation of the K1 and K2 hiring policy be employess in the province of Central Java. Goals to be achieved is to obtain material and data in the framework proposed procurement policy reformulation civil servant particularly from temporary employees. The experiment was conducted by using the approach of law (statutory approach) and approaches the case (case approach). Using primary data and secondary data more emphasis on objectivity and honesty are realized by explaining the purpose of research to the informant. Additionally secret informant’s identity, so that the consequences of the results of this study do not affect the informant who had provided information. The results showed that in the province of Central Java, in the implementation of procurement policies as a problem-solving contractual government empolyee called K1 and K2, beginning with data collection activities, socialization PP 48/2005 jo. PP 43/2007 and its implementation visible to the interaction between institutions or organizations framers with relevant agencies. Interactions can be coordination (coordination meetings), commands / instructions (circulars, technical instructions). Institutionalization and setting honorary workers in Central Java environment problematic minimal because of the following 4 things, (i) Legality officials who appoint honorary varied; (ii) payroll funding not only from the state budget / budget but also from other revenue;(iii) The place of work is not in government agencies but are appointed by the competent authority salary from the state budget / budget; and (iv) A lot of temporary employees who do not meet the provisions of Regulation on age and years of service. To that end, the future recruitment area honorarium need for precise criteria for the task or work performed by a local temporary employees. To be able to make improvements in the planning area management strategies honorary staff, need to know thoroughly the patterns in which the planning strategies in making decisions and actions must be in accordance with the plan to do.